SOCIO-PSYCHOLOGICAL TRAINING FOR THE FORMATION OF PARENT-CHILD RELATIONSHIPS AND THE EMOTIONAL INTERACTION OF A TEACHER WITH A CHILD IN THE CONTEXT OF THE WORK OF A SOCIAL WORKER - Maliar, Olena (Social work and education, 2019)
The article deals with socio-psychological training as one of the most effective and perspective directions of work of a social worker with a family. This training helps to solve a wide range of tasks, primarily related to communication in the family - the focus on correction and development of the system of relations of personality - competence in communicating with the child. In the context of the study, the essence of the concept of training (socio-psychological training) in the work of a social worker was disclosed.There is described a training for parents and teachers about understanding the emotional development of the child and promoting of positive communication. The following methods were used: analysis, generalization of scientific literature on the use of social-psychological training by a social worker in working with family and teachers. The stages of preparation of parents and teachers in participation in social psychological training, which provide positive perception of training sessions with them, are presented. The author describes the structure of the author's social and psychological training on the formation of positive child-parent relationships and the emotional interaction of a teacher with a child of junior school age, which consists of five workshops.It is concluded that the use of social-psychological training with the family in the work of a social worker provides positive perception of parents and teachers of the peculiarities of the social and psychological development of the child and the formation of tolerant communication with others in the adult.